2017
DOI: 10.1007/s00421-017-3543-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an acute dose of omega-3 fish oil following exercise-induced muscle damage

Abstract: Effect of an acute dose of omega-3 fish oil following exercise-induced muscle damageAbstract Purpose: The purpose of this double blind, placebo controlled study was to examine the effect of two fish oil supplements, one high in EPA (750mg EPA, 50mg DHA and one low in EPA (150mg EPA, 100mg DHA), taken acutely as a recovery strategy following EIMD.Methods: Twenty-seven physically active males (26 ± 4 yr, 1.77 ± 0.07 m, 80 ± 10 kg) completed 100 plyometric drop jumps to induce muscle damage. Perceptual (perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 39 publications
(32 reference statements)
0
57
1
1
Order By: Relevance
“…Cytokines can trigger release of acute phase proteins and inflammatory mediators, such as leukotriene and prostaglandin. In a recent study with male subjects, Jakeman et al [37] have shown that acute ingestion of fish oil may inhibit elevation of serum cytokines and markers of muscle damage after jumping exercises. Muscle recovery after exercise influences training adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines can trigger release of acute phase proteins and inflammatory mediators, such as leukotriene and prostaglandin. In a recent study with male subjects, Jakeman et al [37] have shown that acute ingestion of fish oil may inhibit elevation of serum cytokines and markers of muscle damage after jumping exercises. Muscle recovery after exercise influences training adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Both Phillips et al [66] and Tsuchiya et al [68] reported that serum IL-6 reached the peak at 3 d postexercise. Four out of 7 studies found a significant decrement in the n-3 PUFA groups compared to the placebo groups [58,[66][67][68], while others exhibited no differences [61,62] or even an upregulated IL-6 level [60].…”
Section: Othermentioning
confidence: 97%
“…After screening the titles and abstracts of the remaining 31 citations, 15 studies were selected and retrieved for full-text assessment based on the predetermined inclusion criteria, among which 3 were excluded with reasons, 2 were unrelated, and 1 contained duplicate data. Finally, a total of 12 RCTs [57][58][59][60][61][62][63][64][65][66][67][68] were considered eligible for inclusion and went into qualitative and quantitative syntheses. The literature screening process is presented in Figure 1.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations